Tanshinone IIA Improves Acute Gouty Arthritis in Rats through Regulating Neutrophil Activation and the NLRP3 Inflammasome. (19th December 2022) - Xu, Lianjie; Liu, Xiao; Zhang, Yurong; Jia, Tao; Li, Limei; Du, Yan; Chen, Wenhui; Zhang, Shan
Abstract : Objectives . To investigate the prevention and treatment effect of tanshinone IIA (TIIA) on acute gouty arthritis (AGA) and its mechanism. Methods . The anti-AGA effect of TIIA was observed in vivo and in vitro . Neutrophils were isolated from the abdominal cavity of mice, and the anti-AGA effect of TIIA was investigated in a rat model of MSU-induced AGA. The pathological changes of the ankle joint tissues were assessed by H&E. Cytokine and chemokine expression were determined by ELISA and RT-qPCR. The NLRP3 inflammasome pathway protein levels in the ankle joint tissues were evaluated via western blotting. Neutrophil migration was evaluated in air pouch and transwell assays. Immunohistochemistry and immunofluorescence analysis evaluate the release of myeloperoxidase (MPO), neutrophil elastase (NE), and citrullination of histone H3 (CitH3). Beclin-1 and LC3B expressions were determined using western blotting and immunofluorescence. Key Findings . Treatment with TIIA alleviated synovial hyperplasia and neutrophil infiltration, regulated cytokine and chemokine expressions, and inhibited NLRP3 activation in AGA rats, neutrophil migration, MPO, NE, and CitH3 expression, and LC3B and Beclin-1 protein expression. Conclusions . These results demonstrate that TIIA can effectively enhance AGA by focusing on the neutrophils and NLRP3 inflammasome, demonstrating that TIIA may act as a potential helpful agent for AGA.